MENINGKATKAN KEMAMPUAN SAINS ANAK USIA DINI MELALUI PEMBELAJARAN BERBASIS KETRAMPILAN PROSES - Anita Chandra Dewi (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2011)
The purpose of this research is to find out (1) the process of science learning at the kindergarten and (2) the improvement of science mastery of the kindergarten?óÔé¼Ôäós pupils after the process skills are conducted. This research was done at TK Islamic kindergarten of Annisa Bantar Gebang Bekasi, especially at The B Kindergarten with 21 pupils as the objects of research and 3 people as the observers.This research used the action research method of Kemmis MC Taggart with the four components, that is: a) planning, b) action, c) observation, d) reflection. The data was collected by means of interview, observation, and document analysis. The data was analysized qualitatively and quantitatively. The result of the research shows that by using the process skills in science learning. It?óÔé¼Ôäós improving the science mastery of early-aged children, mainly at the Kindergarten B, it was improved. It was showed by the result of t test (22,264) is higher than t critical two tail (2,086). It means the improvement of science mastery of early-aged children is significant.